2022
DOI: 10.3390/healthcare10020308
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to HIV Infection: The Experience of Craiova Regional Centre, Romania

Abstract: Background and objectives: HIV infection in pregnant women can be responsible for a number of consequences during pregnancy, such as: maternal anaemia, miscarriage, low birth weight, and preterm birth. The objectives of this study were to determine the maternal–foetal transmission rate of HIV among pregnant women living with HIV from Craiova Regional Centre in order to assess the risk factors for mother-to-child transmission of HIV and to identify the characteristics of newborns perinatally exposed to HIV. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The pooled MTCT rate of 2.74% for HIV was lower than 3.6% reported in Swaziland, 38 3.5% in Romania, 39 3·1% in Israel, 40 but higher than 1% reported in Oman 41 and 0% reported in Brazil. 42 Although the pooled MTCT rate of 2.74% is reported in this study, this is not a reflection of good PMTCT program in Nigeria because Nigeria still accounts for the highest number of new pediatric HIV infections in the world.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The pooled MTCT rate of 2.74% for HIV was lower than 3.6% reported in Swaziland, 38 3.5% in Romania, 39 3·1% in Israel, 40 but higher than 1% reported in Oman 41 and 0% reported in Brazil. 42 Although the pooled MTCT rate of 2.74% is reported in this study, this is not a reflection of good PMTCT program in Nigeria because Nigeria still accounts for the highest number of new pediatric HIV infections in the world.…”
Section: Discussionmentioning
confidence: 55%
“…The principal findings in this systematic review were that the rate of MTCT of HIV was 2.74% and HBV was 55.49% among mother-infant pairs with mono-infection of HIV and HBV respectively. We identified no completed studies examining The pooled MTCT rate of 2.74% for HIV was lower than 3.6% reported in Swaziland, 38 3.5% in Romania, 39 3•1% in Israel, 40 but higher than 1% reported in Oman 41 and 0% reported in Brazil. 42 Although the pooled MTCT rate of 2.74% is reported in this study, this is not a reflection of good PMTCT program in Nigeria because Nigeria still accounts for the highest number of new pediatric HIV infections in the world.…”
Section: Discussionmentioning
confidence: 85%
“…The yearly number of Romanian newborns in the whole country with perinatal HIV infections has varied in the last 10 years from 6 to 28 cases, meaning between 0.7% and 4.6% of the new cases yearly, distributed by the means of transmission [ 10 ]. The perinatal transmission rate reported in other Romanian centers varied between 3% and 7% [ 16 , 17 , 18 ]. The result of our study, was “zero maternal-fetal infections”, strengthening the regional hope of eradicating HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…No maternal deaths were recorded in our center. At the same time, WHO statistics for Romania indicate zero maternal deaths associated with HIV and an overall maternal mortality rate with a declining trend, up to 5.2/100,000 births [ 16 ]. The perinatal mortality rate declined worldwide, and the discrepancy between children born to HIV-positive and HIV-negative mothers has been narrowed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors, therefore, suggested that addressing these factors can help increase the number of people engaging in HTS services, possibly modifying their engagement in high-risk behaviours. [24] There is demand for HTS (people want to know their HIV serostatus), and demand can also be created when comprehensive services are made available and stigma is reduced. An increasing number of countries are rapidly addressing the quality and quantity of care-related programs.…”
Section: Discussionmentioning
confidence: 99%